Designing Biodegradable and Active Multilayer System by Assembling an Electrospun Polycaprolactone Mat Containing Quercetin and Nanocellulose Between Polylactic Acid Films - Rojas-Sepulveda, A; Lopez de Dicastillo-Bergamo, A; Garrido-Ayala, L; Velasquez, E (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The design of multilayer systems is an innovative strategy to improve physical properties of biodegradable polymers and introduce functionality to the materials through the incorporation of an active compound into some of these layers. In this work, a trilayer film based on a sandwich of electrospun polycaprolactone (PCL) fibers (PCLé) containing quercetin (Q) and cellulose nanocrystals (CNC) between extruded polylactic acid (PLA) films was designed with the purpose of improving thermal and barrier properties and affording antioxidant activity to packaged foods. PCLé was successfully electrospun onto 70 µm-thick extruded PLA film followed by the assembling of a third 25 µm-thick commercial PLA film through hot pressing. Optical, morphological, thermal, and barrier properties were evaluated in order to study the effect of PCL layer and the addition of Q and CNC. Bilayer systems obtained after the electrospinning process of PCL onto PLA film were also evaluated. The release of quercetin from bi-and trilayer films to food simulants was also analyzed. Results evidenced that thermal treatment during thermo-compression melted PCL polymer and resulted in trilayer systems with barrier properties similar to single PLA film. Quercetin release from bi-and trilayer films followed a similar profile, but achieved highest value through the addition of CNC. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.